Seventy Years of FDI Literature: Review, Comparison and Critique - Siddique Hasinul Hussan; Bardai Barjoyai Bin (ECONOMICS, 2023)
International capital movement in the form of Foreign Direct Investment (FDI) by multinational enterprises (MNEs) signifies a widely researched phenomenon in comprehensive review of the FDI literature. Its vastness makes it impossible to fathom its depth, as such the paper highlights what the author considers to be mainstream theories in the domain of empirical studies on FDI. This study critically reviews (FDI) literature over a period of 70 years from 1950 to 2020 to provide a theoretical lens for future research beyond the established models. The discussion covers the mode of FDI inflows, statistical methods applied, theoretical models, contributions to paradigms and empirical papers investigating FDI. Furthermore, the papers selected cover heterogenous geographical regions, while in certain papers FDI has been studied as a dependent variable in others as an independent one. The focus lies on the FDI and its resultant activities of MNEs in the form of subsidiaries to carry out market seeking, strategic asset-seeking and efficiency seeking activities. Though, most researchers have narrowed down to four determinants of FDI i.e., motives of MNEs for undertaking FDI, size of MNEs, entry modes into host country and investments sector recently, many works have applied formal theories to provide a framework for market failure such as holdup problems, non-fulfillment of contracts and related agency costs. It is concluded that FDI has evolved into a significant area of empirical investigation. Overall, the gaps and opportunities in existing literature are identified thereby directions for further research emerge.